1996
DOI: 10.1210/jcem.81.3.8772557
|View full text |Cite
|
Sign up to set email alerts
|

The insulin resistance in women with hyperandrogenism is partially reversed by antiandrogen treatment: evidence that androgens impair insulin action in women.

Abstract: To assess whether androgen excess per se might impair insulin action, insulin sensitivity was measured by a two-step (20 and 80 mU/m2.min) hyperinsulinemic euglycemic clamp combined with indirect calorimetry and tracer glucose infusion in 43 women (13 obese and 30 nonobese) with normal glucose tolerance and clinical evidence of increased androgen action (hirsutism and/or polycystic ovary syndrome) as well as 12 age- and body mass index-matched healthy controls. Hyperandrogenic women were studied basally and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(61 citation statements)
references
References 65 publications
1
56
1
2
Order By: Relevance
“…(62) This is further confirmed by a study on female to male transsexuals that administration of testosterone induces insulin resistance in healthy female subjects. (63) Clinically, a number of antiandrogens including cyproterone acetate, flutamide, spironolacton, and finasteride have been used to treat hyperan-drogenism in women with or without PCOS.…”
Section: Treatment With Antiandrogens In Pcosmentioning
confidence: 71%
See 1 more Smart Citation
“…(62) This is further confirmed by a study on female to male transsexuals that administration of testosterone induces insulin resistance in healthy female subjects. (63) Clinically, a number of antiandrogens including cyproterone acetate, flutamide, spironolacton, and finasteride have been used to treat hyperan-drogenism in women with or without PCOS.…”
Section: Treatment With Antiandrogens In Pcosmentioning
confidence: 71%
“…(54) Although treatment with antiandrogens may improve the lipid profile in PCOS women with hyperandrogenism, (72) the peripheral insulin resistance associated with hyperandrogenism can only be partially reversed. (62) Based on these observations, various insulin-sensitizing agents including metformin and troglitazone have been tried to reduce the insulin resistance and in turn lower the extent of hyperandrogenism in women with PCOS.…”
Section: Treatment With Insulin-sensitizing Agents In Pcosmentioning
confidence: 99%
“…As previously reported, several studies have demonstrated that antiandrogens, as well as reducing androgen levels, may significantly improve insulin resistance and hyperinsulinemia in either obese and non-obese PCOS women. These effects have been observed regardless of the type of drug used, the results observed being substantially similar for spironolactone, 55 flutamide, 54,108 finasteride 54,55 or GnRH agonists. 108 On the other hand, there are no studies investigating the effect of pure antiandrogens on body compartments and fat distribution in these women.…”
Section: Other Drugsmentioning
confidence: 74%
“…The gradual decrease in IR through time may be partly attributed to androgen decline with aging. Indeed, a chicken-and-egg situation exists between IR and hyperandrogenemia in PCOS, and several in vitro and in vivo studies have demonstrated an improvement in IR through androgen reduction (37,38,39). Additionally, in either pre-or postmenopausal normal women, a direct relationship between androgen levels and IR or DM risk has been determined (40,41).…”
Section: Figurementioning
confidence: 99%